Search and Study of Storm Activity on Saturn and Other Planets of the Solar System - Mylostna, K. Y.; Zakharenko, V. V. (Видавничий дім «Академперіодика», 2013)
This paper analyzes the available results of planetary thunderstormresearches in order to assess the possibility of recordingand studying them by low-frequency ground-based radio telescopes,such as the UTR-2, radio interferometer system URAN,and also LOFAR (Low Frequency Array), LWA (Long WavelengthArray) and GURT (Giant Ukrainian Radio Telescope).